2012
DOI: 10.5539/ijps.v4n2p154
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Parent Management Training, Problem-solving Skills Training and the Eclectic Training on Conduct Disorder in Iranian Elementary School Students

Abstract: The present study investigated the effects of parent management training, problem-solving skills training and the eclectic training on symptoms of conduct disorder in Isfahan elementary school students during the educational year 2010-2011. The sample included 40 male pupils (ages 10 to 11) randomly selected assigned to experimental and control groups. Four groups were formed (each group consisted of 10 students), namely parent management training, problem-solving skills training, eclectic training and a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Moreover, behavior therapy administered in the last three months was effective as well. This finding was comparable to other studies which have indicated that using a combination of therapies was effective in treating conduct disorder [5,8,34,62].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, behavior therapy administered in the last three months was effective as well. This finding was comparable to other studies which have indicated that using a combination of therapies was effective in treating conduct disorder [5,8,34,62].…”
Section: Discussionsupporting
confidence: 89%
“…In confirming the above results, the other study examined the effect of parent management training and Problem-solving Skills Training on symptoms of children with CD in Isfahan/Iran between 40 male pupils between 10 to 11 years old [29]. The result of this study demonstrated that parent management training decreased the symptoms of CD.…”
Section: Discussionsupporting
confidence: 70%
“…These studies mainly focused on Cognitive Behavioral Therapy such as the study of Baedi [25] to examine the effects of play therapy on the basis of Cognitive-Behavioral group Therapy for children with aggressive behavior between 7 and 11 years old, the study of Tuisarkani-Ravari [26] to determine the effects of social skills training based on storytelling between 22 girls at primary school between 10 and 11 years old with Conduct Disorder, the other study to evaluate the effects of group therapy based on Cognitive Behavioral play therapy for aggressive children between 8 and 11 years old [27], the later study to examine the effects of group therapy in parent-child relationship on aggression in pre-school children with aggressive behavior [28], and the additional study to determine the effects of Problem-Solving Skills Training and Parent Management Training among 40 students between 10 and 11 years old with CD [29]. Overall, the results of above studies showed that Cognitive-Behavioral Therapy was effective for decreasing aggressive behavior and improvement in social skills.…”
Section: Introductionmentioning
confidence: 99%